Pengaruh Company growth, Debt covenant, IOS, dan Insentif pajak terhadap Konservatisme Akuntansi - Ningsih, Tri Kesuma Setya; Rusmianto, Rusmianto; Pentiana, Destia (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the influence of company growth, debt covenants, investment opportunity sets (IOS), and tax incentives on the application of accounting conservatism in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX). Methodology: This quantitative research uses secondary data from the annual financial reports of 18 infrastructure companies from to 2021-2023, yielding 54 observations. Data were analyzed using multiple linear regression after passing the classical assumption tests. Results: The results indicate that debt covenants, IOS, and tax incentives significantly affect accounting conservatism. Debt covenants and IOS have a negative influence, whereas tax incentives have a positive effect. However, company growth had no significant effect. Simultaneously, these four variables influence accounting conservatism, with an Adjusted R² value of 75.9%. Conclusion: This study concludes that pressure from debt agreements, high investment opportunities, and tax incentives encourage infrastructure companies to adopt more conservative and cautious financial reporting. Limitation: The study's scope is limited to the infrastructure sector over a three-year period, so the findings may not be generalizable to other sectors or timeframes. Contribution: These findings provide regulators and practitioners with input on the drivers of accounting conservatism, which can enhance the credibility of financial statements and maintain investor confidence in the infrastructure sector.